The Effects of Akkermansia Munciniphila on Serotonin and Fetuin-A Hormone Levels and Some Biometric Parameters in Obese Patients - Alajeeli, Fakhri (Iraqi Journal of Science, 2020)
The objective of the present study is to determine the anti-obesity effects of Akkermansia munciniphila on some biometric measurements. 40 patients were divided into two groups, each with 20 patients; G1 group consumed the probiotic of A. munciphila and G2 consumed placebo capsules. The results showed significant effects on the body weight (p≤ 0.001), which was reduced by a range of -2.29 to -0.7, whereas non-significant differences were observed in the Waist circumferance . The study also showed significant differences (p≤0.001) between the two groups in the levels of cholesterol (287 vs. 285 mg/dl) , whereas the level of Triglyceride significantly decreased in the treated patients (p≤0.001). No significant differences were observed in the concentration of fat. There were also significant differences in the levels of fetuin-A (p≤0.020) and serotonin ( p≤ 0.039 ). The consumption of the probiotic of A. muciniphila was proved to be beneficial for human health, while further studies are needed to explore more effects.